Nitrogen Doped Carbons Derived From Graphene Aerogel Templated Triazine-Based Conjugated Microporous Polymers for High-Performance Supercapacitors - Peng, Lan; Guo, Qianyin; Ai, Zhaolin; Zhao, Yan; Liu, Yunqi; Wei, Dacheng (Frontiers in Chemistry, 2019)
Conjugated microporous polymers (CMPs) have attracted intensive attention owing to their permanent nanoporosity, large surface area and possibility for functionalization, however their application in energy storage suffers from poor conductivity and low hetero-atom content. Here, we demonstrate a hybrid of conjugated microporous polymers and grephene aerogel with improved conductivity. After treating at 800 °C in NH3, the nitrogen content increases to 9.8%. The resulting microporous carbon exhibits a significant rise in supercapacitive performance up to 325 F g−1, 55% higher than pristine triazine-based CMPs, with energy density up to 12.95 Wh kg−1. Moreover, it has high stability with 99% retention after 10000 cycles at 5 A g−1. The synergy of hierarchical porous structure, graphene-based conduction path and high percentage of hybridization with nitrogen ensures effective ion/electron transport and diffusion, making NH3-treated graphene aerogel/CMP hybrid a promising electrode material in high-performance supercapacitor.